1998
DOI: 10.2307/44152967
|View full text |Cite
|
Sign up to set email alerts
|

Moore-Smith Limits and the Henstock Integral

Abstract: An integral is defined using the Moore-Smith limit and this new integral is compared to the Henstock integral.It is well-known though not easily found in the literature that the Riemann integral can be defined by Moore-Smith limit using divisions. Then many properties of the Riemann integral will have straightforward proofs. In this paper, we shall investigate whether the Henstock integral can also be defined by means of Moore-Smith limit involving δ-fine divisions. We assume that the reader is familiar with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The H 1 -integral has been introduced by Garces, Lee, and Zhao [3], in an attempt to define an integral with nearly the Kurzweil-Henstock integral power, but in terms of Moore-Smith limits. Later advances in the theory of H 1 -integration have shown that this challenge was not successful in some sense.…”
Section: H 1 -Integralmentioning
confidence: 99%
“…The H 1 -integral has been introduced by Garces, Lee, and Zhao [3], in an attempt to define an integral with nearly the Kurzweil-Henstock integral power, but in terms of Moore-Smith limits. Later advances in the theory of H 1 -integration have shown that this challenge was not successful in some sense.…”
Section: H 1 -Integralmentioning
confidence: 99%
“…23-27, pp. 113-138] and [3], [8], [9]. In other words, the integral is defined by way of refinements of partitions and the integral is the Moore-Smith limit of the Riemann-Stieltjes sums using the directed set of partitions.…”
Section: Introductionmentioning
confidence: 99%